What’s Among and Between Us: Mining the Arts for Pedagogies of Deep Relation (LEARNing Landscapes, 2021)
In this paper, I share results of collaborative inquiry with youth and teachers into how the arts can create more relational learning spaces in the classroom. I offer a framework for relational teaching and learning through the arts guided by the questions: Who am I? Who are you? And who are we? Through these dimensions, I explore how arts-based practice can support new ways of being in the classroom, where teaching creates conditions for students to be “among and between”: in relation to the material, the teacher, and importantly, to themselves, to each other, and to the world around them.
Keywords: arts; arts-based; literacy; relational learning; pedagogy